Exploring the Intersections of Technology, Crime, and Terror. - Holt, Thomas J. (Terrorism & Political Violence)
The Internet and computer-mediated communications (CMCs) have drastically changed the way that individuals communicate and share information across the globe. Over the last two decades, financial institutions, private industry, and governments have come to rely on technology in order to access sensitive data and manage critical infrastructure, such as electrical power grids. As a consequence, the threat posed by cybercriminals has increased dramatically and afforded significant opportunities for terrorist groups and extremist organizations to further their objectives. The complex and intersecting nature of both crime and terror make it difficult to clearly separate these issues, particularly in virtual environments, due to the anonymous nature of CMCs and challenges to actor attribution. Thus, this study examines the various definitions for physical and cyberterror and the ways that these activities intersect with cybercrime. In addition, the ways that terrorists and extremist groups use the Internet and CMCs to recruit individuals, spread misinformation, and gather intelligence on various targets are discussed. Finally, the uses of computer hacking tools and malware are explored as a way to better understand the relationship between cybercrime and terror.